The Goosander Mergus merganser population breeding in the Alps and its connections to the rest of Europe - Keller, Verena (Wildfowl, 2009)
The main range of the Goosander Mergus merganser in Europe stretches from Norway to northern Russia. Outside this main range, breeding populations exist in Iceland, Britain and the Balkans. In the Alps, the birds breed mainly in Switzerland and southern Germany (Bavaria). This paper compiles evidence from different disciplines to determine the conservation status of the Central-West European (Alpine) population of Goosander, in particular whether it is isolated from other Goosander populations. Recoveries of ringed birds showed that the Goosanders breeding in the Alpine region, estimated at c. 1,000–1,400 pairs in 1998, are augmented by birds from northern Europe during the winter months. Molecular analysis of female-inherited mtDNA indicated a strong genetic differentiation among European breeding populations, whereas no significant differences were found at nuclear DNA markers, indicating at least some interchange between populations. The evidence from the various studies reinforces the view that the Central-West European (Alpine) population of Goosander should be considered as a separate population and conservation unit.